1999
DOI: 10.1105/tpc.11.5.793
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Markers and Cell Cycle Inhibitors Show the Importance of Cell Cycle Progression in Nematode-Induced Galls and Syncytia

Abstract: Root knot and cyst nematodes induce large multinucleated cells, designated giant cells and syncytia, respectively, in plant roots. We have used molecular markers to study cell cycle progression in these specialized feeding cells. In situ hybridization with two cyclin-dependent kinases and two cyclins showed that these genes were induced very early in galls and syncytia and that the feeding cells progressed through the G2 phase. By using cell cycle blockers, DNA synthesis and progression through the G2 phase, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
161
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 189 publications
(173 citation statements)
references
References 47 publications
10
161
1
1
Order By: Relevance
“…Because Mi-mediated resistance is effected within a narrow time window after RKN invasion (Dropkin, 1969), this result was not surprising. We also found no differences in gene expression (Hutangura et al, 1999;Bird and Koltai, 2000); 3, pathogenesis-related genes (Bowles, 1990); 4, transport (Hammes et al, 2005); 5, nucleic acid binding; 6, (I) shikimate (Doyle and Lambert, 2002); 7, (Y) cell cycle (Niebel et al, 1996;de Almeida Engler et al, 1999); 8, aquaporin, water channel-related genes (Opperman et al, 1994); 9, (X) peroxidase; 10, cell wall (Bird,1974); 11, GC genes ; 12, (S) ribosome-related genes; and 13, genes with unknown function. Annotations were searched with keywords (Supplemental Table S2) to identify genes to categorize.…”
Section: The Root Transcriptome At Rkn Egg Layingmentioning
confidence: 89%
See 1 more Smart Citation
“…Because Mi-mediated resistance is effected within a narrow time window after RKN invasion (Dropkin, 1969), this result was not surprising. We also found no differences in gene expression (Hutangura et al, 1999;Bird and Koltai, 2000); 3, pathogenesis-related genes (Bowles, 1990); 4, transport (Hammes et al, 2005); 5, nucleic acid binding; 6, (I) shikimate (Doyle and Lambert, 2002); 7, (Y) cell cycle (Niebel et al, 1996;de Almeida Engler et al, 1999); 8, aquaporin, water channel-related genes (Opperman et al, 1994); 9, (X) peroxidase; 10, cell wall (Bird,1974); 11, GC genes ; 12, (S) ribosome-related genes; and 13, genes with unknown function. Annotations were searched with keywords (Supplemental Table S2) to identify genes to categorize.…”
Section: The Root Transcriptome At Rkn Egg Layingmentioning
confidence: 89%
“…Collectively, these experiments have revealed that genes regulating the cell cycle (Niebel et al, 1996;de Almeida Engler et al, 1999), cell wall synthesis (Niebel et al, 1993;Goellner et al, 2001;Vercauteren et al, 2002), and transcription regulation are up-regulated in GCs. Gheysen and Fenoll (2002) provide a detailed review of the approximately 50 genes known to be up-regulated and a few that are repressed.…”
mentioning
confidence: 99%
“…Plant growth conditions were performed according to Mangeon et al 14 Transformation procedures were performed according to Clarke et al 15 Histochemical GUS assays were performed according to Mangeon et al 16 Nematode inoculation was conducted as described in Almeida-Engler et al 12 Five to 10 plants were examined for the presence of GUS activity. Hydroxyurea and Oryzalin treatments were performed as previously described 12 with the following modifications: concentration of hydroxyurea and oryzalin was 100 mg/mL and 15mM, respectively, and incubation time was 16-20 hours.…”
Section: Methodsmentioning
confidence: 99%
“…In Arabidopsis, cytological observations and molecular markers assays have shown that both root-knot and cyst nematode infection induces large multinucleated feeding cells in the roots, where the parasites induce cycles of cell divisions and DNA endoreduplication. 11,12 Transgenic plants transformed with AtDBP1 promoter-GUS construct were infected with Meloidogyne incognita and Heterodera schachtii and GUS expression observed after infection. With both parasites, an increase in GUS expression could be detected 2 days after infection ( Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation